160 The impact of exercise and diet intervention on left atrial function in type 2 diabetes: results from a randomised study. (4th June 2021) - Alfuhied, Aseel; Gulsin, Gaurav; Brady, Emer; Parke, Kelly S; Athithan, Lavanya; Henson, Joseph; Redman, Emma; Yates, Thomas; Davies, Melanie; Marsh, Anna-Marie; McCann, Gerry; Singh, Anvesha
Abstract : Introduction: The effects of low-energy diet or exercise on cardiovascular function in younger adults with type 2 diabetes (DIASTOLIC) study showed a significant improvement in left ventricle peak early diastolic strain rate in response to a 12-week programme of aerobic exercise in patients with type-2 diabetes (T2D). The impact of exercise and a low-calorie meal replacement plan (MRP) on left atrial (LA) function in T2D has not yet been explored. We investigated the effect of lifestyle intervention on LA volumetric and strain parameters by cardiac magnetic resonance (CMR) imaging. Methods: The DIASTOLIC study was a prospective, randomised, open-label, blind endpoint trial. Obese participants with T2D (aged 18–65 years) were randomized to a 12-week intervention of: aerobic exercise training or low energy (≈810kcal/day) MRP. CMR was performed at baseline and week-12. Images were analysed using Medis v3.1. LA strain and strain rate (LAS/SR) were assessed using Feature Tracking (QStrain v2.0), corresponding to LA reservoir (LAS/SR-r), conduit (LAS/SR-cd), and booster pump (LAS/SR-bp) using 4- and 2-chamber standard steady-state free precession cine images, and average values calculated. LA volumes (LAV) were measured on 4 a d 2-chamber cine images and LA emptying fraction (LAEF) was calculated using biplane area-length method (QMass v8.1) for total, passive and active EF. Results: 45 participants with T2D completed the trial and had analysable LA cine images (22 exercise and 23 MRP). There were no significant changes in the standard assessment of LA volumetric function (LAV/LAEF) measured on CMR or in LV filling pressure (E') measured on echocardiography, in either group. In the MRP group, there were significant reductions in BMI (4.8 kg/m2), mean systolic blood pressure (SBP) (13mmHg), and a significant increase in LAS-r and LAS-bp (29.9±7.0 to 32.3±7.0, p=0.036 and 14.6±5.3 to 17.2±3.7, p=0.034) (see Table). The exercise arm showed a small reduction in BMI (0.8kg/m2), no significant change in BP and a significant improvement in LASR-bp (-1.19±0.3 to -1.32±0.4; p=0.041). Conclusion: A low-calorie MRP led to significant weight loss and improved SBP, with associated improvement in LA reservoir and contractile function on CMR strain assessment. LAS could detect early LA reverse remodelling post-lifestyle intervention in young adults with T2D despite no change in volumetric measurements. Conflict of Interest: None